2019
DOI: 10.21203/rs.2.15470/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affecting HBV Vaccination in a Medical Training College in Kenya: A Mixed Methods Study

Abstract: Background : Hepatitis B Virus (HBV) is highly endemic in Sub-Saharan Africa with 70 to 90% of the population becoming infected before the age of 40 years. Healthcare workers (HCWs) including healthcare students (HCSs) are at an increased risk of contracting HBV due to occupational exposure. HCSs are especially at a high risk because of their inexperience with infection control procedures and insufficient knowledge about the level of risk when dealing with patients. Despite the availability of an effective vac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…1 However, in a previous Kenyan study, the major reason for not receiving the recommended doses was the non-availability of the vaccine. 13 In our findings, the reasons were different as the majority revealed that lack of awareness of the HBV vaccine was the greatest reason for their non-uptake of the vaccine. This finding is understandable because our present study was performed on a general antenatal (pregnant) women population while the previous Nigerian study 1 and Kenyan study 13 were on health workers.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…1 However, in a previous Kenyan study, the major reason for not receiving the recommended doses was the non-availability of the vaccine. 13 In our findings, the reasons were different as the majority revealed that lack of awareness of the HBV vaccine was the greatest reason for their non-uptake of the vaccine. This finding is understandable because our present study was performed on a general antenatal (pregnant) women population while the previous Nigerian study 1 and Kenyan study 13 were on health workers.…”
Section: Discussionmentioning
confidence: 57%
“…We defined HBV vaccination status as: (i) no vaccination when no dose was received; (ii) partial vaccination when one or two doses were received; and (iii) full vaccination when three or four doses were received. 13…”
Section: Full Surveymentioning
confidence: 99%